The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/nphys596
|View full text |Cite
|
Sign up to set email alerts
|

Spin–valley phase diagram of the two-dimensional metal–insulator transition

Abstract: Using symmetry breaking strain to tune the valley occupation of a two-dimensional (2D) electron system in an AlAs quantum well, together with an applied in-plane magnetic field to tune the spin polarization, we independently control the system's valley and spin degrees of freedom and map out a spin-valley phase diagram for the 2D metal-insulator transition. The insulating phase occurs in the quadrant where the system is both spin-and valley-polarized. This observation establishes the equivalent roles of spin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
53
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 35 publications
(66 reference statements)
6
53
1
Order By: Relevance
“…It is possible that because the UCF noise involves interference between two Feynman propagators, it is more likely to be affected by the localized spins than the WL correction which is determined by a single self intersecting propagator. Note that we have not discussed spatial inhomogeneity or clustering in the distribution of dopants which can lead to coexistence of localized and delocalized phases [14], impact of multiple valleys [39,40], or the inter-site Coulomb interaction [34,35,41] which are unlikely to affect the time reversal symmetry. In summary, magnetoconductivity and noise measurements reveal an unexpected spontaneous breaking of time reversal symmetry in 2D electron systems hosted in atomically confined Si:P and Ge:P crystals.…”
Section: ≈ 10mentioning
confidence: 99%
“…It is possible that because the UCF noise involves interference between two Feynman propagators, it is more likely to be affected by the localized spins than the WL correction which is determined by a single self intersecting propagator. Note that we have not discussed spatial inhomogeneity or clustering in the distribution of dopants which can lead to coexistence of localized and delocalized phases [14], impact of multiple valleys [39,40], or the inter-site Coulomb interaction [34,35,41] which are unlikely to affect the time reversal symmetry. In summary, magnetoconductivity and noise measurements reveal an unexpected spontaneous breaking of time reversal symmetry in 2D electron systems hosted in atomically confined Si:P and Ge:P crystals.…”
Section: ≈ 10mentioning
confidence: 99%
“…In the so-called Dirac materials like graphene, two energy bands, corresponding to two equivalent sublattices, intersect linearly at different positions in the momentum space, providing multiple valley degeneracy. Since the valley degeneracy is balanced by crystal symmetry, producing a valley-selective current usually requires breaking crystal symmetry by, e.g., strain [1][2][3]. However, a recent study on a three-dimensional (3D) Dirac material, bismuth, demonstrated that a rotating magnetic field modulates the contribution of each valley to the conduction and also reveals the field-induced valley polarization [7][8][9].…”
mentioning
confidence: 99%
“…Controlling the valley degree of freedom can be an effective way to modulate charge conduction and to induce intriguing phases [1][2][3][4][5][6][7][8][9][10]. In the so-called Dirac materials like graphene, two energy bands, corresponding to two equivalent sublattices, intersect linearly at different positions in the momentum space, providing multiple valley degeneracy.…”
mentioning
confidence: 99%
“…This apparent metal insulator transition (MIT) is marked by a "critical carrier density", n c which characterizes the crossover from the higherdensity metallic temperature dependence of the resistivity to the lower-density insulating temperature dependence. For n > n c , the system exhibits a metallic behavior (dρ/dT>0) while for n < n c , the resistivity increases with decreasing temperature and dρ/dT<0 in the insulating phase.In the past twenty years, MIT has been observed in a wide variety of 2D carrier systems such as n-Si MOSFETs [3], n-GaAs [5, 6], p-GaAs [7-9], n-Si/SiGe [10, 11], pSi/SiGe [12, 13] and n-AlAs [14,15]. In the current work we present the first experimental observation of 2D MIT in a narrow gap semiconductor, namely, 2D electrons confined in InAs quantum wells.…”
mentioning
confidence: 99%
“…In the past twenty years, MIT has been observed in a wide variety of 2D carrier systems such as n-Si MOSFETs [3], n-GaAs [5, 6], p-GaAs [7-9], n-Si/SiGe [10, 11], pSi/SiGe [12, 13] and n-AlAs [14,15]. In the current work we present the first experimental observation of 2D MIT in a narrow gap semiconductor, namely, 2D electrons confined in InAs quantum wells.…”
mentioning
confidence: 99%